Sporting habits of students at the University of debrecen Centre for Agricultural Sciences - Pfau, Christa (Acta Agraria Debreceniensis, 2014)
In 2007, a new sport strategy was implemented, (XXI National Sportstrategy), which analyses the current conditions in recreational sports in Hungary and describes its developmental potentials. Additionally, last year a new concept for university sport was introduced (Hajos Alfred Program), having as its most important goal, to develop the recreational sporting activities within the universities’ environment. The latter is of high importance, as this is the last period, when, on an institutional level, we can establish and enhance the need for physical activity among young generations. In this study recreational sport is analysed in the University of Debrecen Faculty of Applied Economics and Rural Development. The purpose of the study was to analyse data on the sporting habits of the faculty students, their preference of where they like to exercise, within or outside of the university campus, and the reasons which can be found behind these preferences. Moreover, this study aimed to evaluate the service quality offered in university recreational sports. Data collection was completed on a paper based questionnaire, 42 closed-type questions were included and a total of 123 students completed it. Based on the results, college students usually complete their competitive level sport activity when they enter college and they continue this activity on a recreational level. Almost two third of them choose to exercise in places outside of the university campus. For those who choose university facilities for their recreational exercise, they do so because; it is usually cheaper and closer to access. In the service quality results we see, that females are less satisfied with teaching staff quality than males, it may be possible that females need more and more effective implementations in order for the universities to better satisfy their needs for physical activity.